2019
DOI: 10.1111/apt.15294
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year effectiveness and safety of vedolizumab therapy for inflammatory bowel disease: a prospective multi‐centre cohort study

Abstract: Summary Background Cohort studies have described the short‐term effectiveness and safety of vedolizumab in treating patients with Crohn's disease (CD) and ulcerative colitis (UC), but data beyond 1 year are lacking. Aim To assess the effectiveness and safety of vedolizumab after 162 weeks in patients with UC and CD. Methods Between June and December 2014, 294 patients including 173 patients with CD and 121 with UC were treated with vedolizumab induction therapy. Among them, 149 continued to be treated with ved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 27 publications
10
62
2
Order By: Relevance
“…The primary endpoint was steroid-free clinical remission at weeks [12][13][14][15][16]. Clinical remission was defined as a partial Mayo Clinic score ≤2, with a combined stool frequency and rectal bleeding subscore ≤1.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary endpoint was steroid-free clinical remission at weeks [12][13][14][15][16]. Clinical remission was defined as a partial Mayo Clinic score ≤2, with a combined stool frequency and rectal bleeding subscore ≤1.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…9 Real-world studies allow bridging of some data gaps by describing patient experiences that are lacking in clinical trials that tend to exclude certain groups of patients. [10][11][12] Real-world experience series bring important data on the effectiveness and safety of new therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Patients from the pivotal phase III clinical studies (GEMINI) could be included in the long‐term open‐label studies (GEMINI‐LTS) and these trials indicated that the effectiveness of vedolizumab remained fairly stable in patients who responded to vedolizumab induction . However, only one study presented the safety and effectiveness results beyond 1 year in a real‐world population . In this study, the steroid‐free clinical remission rate for UC remained fairly stable beyond the first year of treatment, whereas the steroid‐free clinical remission rate of patients with CD tended to decrease over time.…”
mentioning
confidence: 79%
“…Previous studies have shown that disease remission prior to conception and throughout pregnancy is crucial for favourable pregnancy outcomes . In order to achieve disease remission, patients with IBD are frequently treated with biological therapies such as vedolizumab (VDZ), a monoclonal antibody directed against the α4β7 integrin—mucosal vascular addressin cell adhesion molecule 1 (MAdCAM‐1) interaction in the gut . By blocking this interaction, VDZ inhibits the trafficking of gut‐homing lymphocytes .…”
Section: Introductionmentioning
confidence: 99%
“…2 In order to achieve disease remission, patients with IBD are frequently treated with biological therapies such as vedolizumab (VDZ), a monoclonal antibody directed against the α4β7 integrin-mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) interaction in the gut. [3][4][5][6] By blocking this interaction, VDZ inhibits the trafficking of gut-homing lymphocytes. 3 However, data on the use of VDZ during conception and pregnancy remain sparse.…”
Section: Introductionmentioning
confidence: 99%